2014
DOI: 10.3354/meps10701
|View full text |Cite
|
Sign up to set email alerts
|

Predators of the destructive sea urchin Strongylocentrotus droebachiensis on the Norwegian coast

Abstract: In central Norway, populations of the green sea urchin Strongylocentrotus droebachiensis are collapsing, but the factors controlling its population density have not yet been elucidated. Through field sampling, we identified several sea urchin predators and investigated their predation rates on recently settled S. droebachiensis in laboratory experiments. Tethering experiments in kelp forest and on barren ground study sites in the area where sea urchin populations are collapsing confirmed predation by some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 53 publications
3
46
0
2
Order By: Relevance
“…Both Cancer spp. and Necora spp., more abundant in Roscoff, can forage significantly on large echinoderms and play a key role in their regulation (Freire and Gonzalez-Gurriaran, 1995;Ramsay et al, 2000;Steneck et al, 2004;Fagerli et al, 2014). However, given the absence of Echinus esculentus and Marthasterias glacialis in Roscoff, any contribution to the decapod diets cannot be inferred.…”
Section: Hypotheses About Processes Involved In Observed Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Cancer spp. and Necora spp., more abundant in Roscoff, can forage significantly on large echinoderms and play a key role in their regulation (Freire and Gonzalez-Gurriaran, 1995;Ramsay et al, 2000;Steneck et al, 2004;Fagerli et al, 2014). However, given the absence of Echinus esculentus and Marthasterias glacialis in Roscoff, any contribution to the decapod diets cannot be inferred.…”
Section: Hypotheses About Processes Involved In Observed Patternsmentioning
confidence: 99%
“…However, given the absence of Echinus esculentus and Marthasterias glacialis in Roscoff, any contribution to the decapod diets cannot be inferred. Since these predators are not echinoderm specialist, it seems improbable that their densities are sufficient enough to control, even collapse, alone large echinoderm populations at Roscoff site (Miller, 1985;Sivertsen, 2006), but information about echinoderm recruitments and predation-rate on young stages (Fagerli et al, 2014) is lacking in the area. Multi-scale spatio-temporal variability of large echinoderms population can be altered, at different life history stages, by several crossed factors including the nature of the substratum (Laur et al, 1986;Hamel and Mercier, 1996;Balch and Scheibling, 2000), the depth (Reid, 1935;Jones and Kain, 1967;Comely and Ansell, 1988;Verling et al, 2003), the food availability (Laur et al, 1986;Tuya and Duarte, 2012), the predation pressure (Steneck et al, 2004;Estes et al, 2011), the temperature and epizootics (Scheibling and Stephenson, 1984).…”
Section: Hypotheses About Processes Involved In Observed Patternsmentioning
confidence: 99%
“…Scheibling and Robinson (2008) similarly found that sculpins (Myoxocephalus octodecemspinosus) did not consume North Atlantic juvenile S. droebachiensis in the laboratory, but cancrid (Cancer irroratus) and hermit (Pagurus acadianus) crabs were voracious predators. In the North Atlantic, cancrid crabs have been identified as key predators of juvenile and adult S. droebachiensis in the field (Steneck et al 2013;Fagerli et al 2014), and are hypothesized to have replaced large predatory fishes as the major predators controlling sea urchin abundance in the Gulf of Maine (Steneck et al 2004). This shift in species interactions is purported to have occurred due to an increase in crab abundance following the collapse of finfish populations (Steneck et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In the North Atlantic, juvenile S. droebachiensis are subject to intense predation by hermit crabs (Pagurus acadianus), true crabs (Cancer spp. ), shrimp (Crangon septemspinosa), and demersal fishes (e.g., cunner Tautogolabrus adspersus) (Scheibling and Hamm 1991;McNaught 1999;Scheibling and Robinson 2008;Fagerli et al 2014;. Survival of juvenile S. droebachiensis in the Northwest Atlantic is closely tied to the availability and suitability of three-dimensional spatial refuges that provide protection from predators, such as spaces within kelp holdfasts (anchoring structures of kelps) ) and the interstices of cobbles (Scheibling and Hamm 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Rising temperatures cause a decrease in physical disturbance by ice and a northward expansion and higher abundances of many boreal species (Weslawski et al 2011 and references therein). For example, benthic predatory crabs such as Cancer pagurus and H. araneus show increasing densities at the Norwegian and western Svalbard coast, respectively (Woll et al 2006;Berge et al 2009;Fagerli et al 2014). Due to higher consumer occurrence, we expect that new predator-prey interactions will develop in the future.…”
Section: Discussionmentioning
confidence: 99%